South Africa : A Smallholder’s Innovative Approach to Producing and Exporting Fruit - Hart, Tim (World Bank, Washington, DC, 2012)
Exporting deciduous fruit from the Western Cape Province of South Africa to markets in Europe, North America and Asia contributes significantly to the province's Gross Domestic Product. The main export producers are large-scale farmers. Even with the change in discriminatory legislation and practices in South Africa after 1994, few smallholder farmers have penetrated this market. The few smallholders who manage to export their fruit do so through collective or individual arrangements with large-scale commercial operations. One such farmer is Aubrey Billet from Haarlem. He started exporting apples in the 1970s. Over the decades, he developed his own knowledge and innovations in both fruit production and socio-economic arrangements and was able to continue exporting most of his annual apple crop. This article discusses the lessons learned from this farmer's grafting experiments.